The Impact of Outdoor Activity-Based Learning on Elementary School Students' Motivation and Social Skills Development (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study examines the impact of outdoor activity-based learning on student motivation, responsibility, and cooperation in physical education, focusing on two specific activities: Pirates’ Treasure and Team Tail Tag. The increasing recognition of outdoor learning as a tool to enhance both cognitive and social development in elementary education provides the backdrop for this research. The purpose of the study was to investigate how different outdoor activities affect students' learning motivation, particularly in relation to their levels of responsibility and cooperation. A total of 48 students from an elementary school in Ampenan participated, categorized into four treatment groups based on pre-assessed responsibility and cooperation levels. The study employed a 2x2 factorial experimental design, with pretest and posttest assessments to measure changes in motivation. The findings revealed that students with high responsibility and cooperation (A1B1) showed the greatest improvement in motivation when engaging in Pirates’ Treasure, while those with higher cooperation, particularly in Team Tail Tag (A2B2), exhibited the most significant gains. The study also identified a significant interaction between activity type and students’ social traits, suggesting that outdoor activities that promote collaboration are more effective in increasing motivation, particularly for students with initially lower levels of cooperation. However, the research also highlighted several challenges, including limited resources, inadequate teacher training, and resistance to integrating outdoor learning in the curriculum. The study recommends further exploration of the long-term effects of outdoor activities, the effectiveness of various outdoor learning methods, and strategies to overcome implementation barriers, particularly through teacher training and resource allocation.